Aproximación al modelo de gestión mancomunado de la cuenca del río Portoviejo para la reducción de riesgos presentes y futuros (Tema Central) - Velasco Pazmiño, Cristopher (2022)
This study analyzes the relevance of the creation of cooperative units for a better management of the competence of the GAD (Autonomous Decentralized Government) and its contribution to the reduction of present and future risks. There is an analysis on how, since the creation of the cooperative unit for the basin of the Portoviejo river, new efforts and actions have appeared seeking to create beneficial results on risk reduction, especially regarding adverse events such as floods, landslides, drought, wildfires and others. There was a qualitative conceptual approach using a descriptive analytic method, and an analysis of the regulations involved for the creation of the cooperative unit and the modalities used for its management. The main result is evidence of the cooperative processes to handle the risks in the basin which constitutes a mechanism that strengthens the management of the competencies of the municipalities and enables a joint access to climatic financing and helps reduce the risk conditions of the territories in order to improve the adaptive capacity of the population.